HUMANISM VALUES DEPICTED IN LAU KAWAR AS A STRATEGY OF STUDENTâ€™S CHARACTER VALUE - Purba, Rotua; Munthe, Yessi Devi Yulia; Tarigan, Lisma Diana; Situmorang, Artania; Sembiring, Yenita (Journal of Teaching of English, 2021)
This study aims to examine the values of humanism contained inÂ  Legend of Lau Kawar and how the process of applying the character values contained in Lau Kawar in the learning process. The values of humanism are the meanings contained in humanism in forming humans with integrity, having awareness, freedom, and responsibility as human nature. This study seeks to answer research questions; What are the character values found in Lau Kawar and how is the implementation of the character values found in Lau Kawar in the learning process. The object of this research is UPT SMP Negeri 21 Medan and the participants in this study were two informants from Lau Kawar village. This research shows that the vision and mission of the 2013 curriculum to shape students' character is not in accordance with reality. This research method uses qualitative methods with direct data collection. The current study concludes that there are several values of humanism in the Legend of Lau Kawar that can be implemented in the learning process to form good student characters, therefore the use of humanism values in the Legend of Lau Kawar must be taken into account by teachers and the school to shape characterstudents in accordance with the objectives of the 2013 curriculum.